Method for producing silicon nitride sintered body
By controlling the solid solution oxygen amount and form of silicon nitride crystal particles in the sintered silicon nitride body, the problem of the destiny of bearing balls when rotating at high speed is solved, and higher durability and mechanical strength are achieved.
Patent Information
- Application Number
- CN202510170591.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-03-16
- Filing Date
- 2023-03-03
- Publication Date
- 2025-04-15
AI Technical Summary
During high-speed rotation, the durability of the bearing balls made of existing silicon nitride sintered bodies may be reduced, especially in the case of large radial loads, thrust loads and torque loads.
By controlling the solid solution oxygen amount of silicon nitride crystal particles, the average value in the 20 μm×20 μm region of any cross-section is ensured to be 0.2 wt% or more, and the average value of the length diameter is ensured to be 0.1 μm or more and 10 μm or less in the 50 μm x 50 μm region, and the average value of the aspect ratio is 1.5 or more and 10 μm or less.
The durability and mechanical strength of the silicon nitride sintered body under high-speed rotation conditions are improved, and the excellent performance of bearing balls under high load conditions is ensured.
Smart Images

Figure CN119822852A_ABST
Abstract
Description
[0001] This application is a divisional application of an invention patent application with an application date of March 3, 2023, an application number of 202380010379.1, and an invention name of "Silicon nitride sintered body and wear-resistant component using the same". Technical Field
[0002] The embodiments described below mainly relate to a silicon nitride sintered body and a wear-resistant member using the same. Background Art
[0003] Silicon nitride sintered bodies are used for wear-resistant components. Wear-resistant components are used in the fields of bearing balls, rollers, roller materials, compressor impellers, gas turbine blades, engine parts, friction stir welding tool components, etc. Roller materials are used for rolling. Engine parts are, for example, cam rollers.
[0004] For example, Japanese Patent No. 5362758 (Patent Document 1) discloses a silicon nitride sintered body in which titanium nitride particles having an aspect ratio of 1.0 to 1.2 are dispersed. In Patent Document 1, the aspect ratio and particle size of the titanium nitride particles are controlled. In addition, in Japanese Patent No. 6400478 (Patent Document 2), the area ratio of the grain boundary phase and the aspect ratio of the silicon nitride crystal particles are controlled. In Patent Document 2, in order to control the area ratio of the grain boundary phase, an oxidized silicon nitride powder is used.
[0005] In Patent Document 1, the wear resistance test of the bearing ball was conducted at a maximum contact stress of 5.9 GPa and a rotation speed of 1200 rpm. In addition, in Patent Document 2, the wear resistance test of the bearing ball was conducted at a maximum contact pressure of 5.1 GPa and a rotation speed of 1200 rpm. The bearing balls described in Patent Document 1 and Patent Document 2 both showed excellent durability.
[0006] In recent years, high-speed rotation has been required for bearings. The loads applied to bearings include radial loads, thrust loads, and moment loads. Radial loads are loads applied in a direction perpendicular to the rotation axis (circumferential direction of the rotation axis). In addition, thrust loads are loads applied in a direction parallel to the rotation axis (axial direction of the rotation axis). Moment loads are loads generated by the eccentricity of the rotation axis.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent No. 5362758
[0010] Patent Document 2: Japanese Patent No. 6400478
[0011] Patent Document 3: Japanese Patent Application Publication No. 2022-71426
[0012] Patent Document 4: International Publication No. 2016 / 047376 Summary of the invention
[0013] Problems to be solved by the invention
[0014] If the rotation speed of the bearing is increased, the radial load, thrust load and moment load will increase. The durability of the bearing using the bearing balls made of the conventional silicon nitride sintered body is sometimes reduced at high speed. The solution was studied and it was found that the amount of dissolved oxygen in the silicon nitride crystal particles has an effect.
[0015] The present invention is an invention for coping with such a problem, and provides a silicon nitride sintered body in which the amount of dissolved oxygen is controlled.
[0016] Means for solving problems
[0017] The silicon nitride sintered body of the embodiment comprises silicon nitride crystal particles and grain boundary phases. In a 20 μm×20 μm region of any cross section, the average value of the amount of dissolved oxygen in the silicon nitride crystal particles is 0.2 wt% or more. In a 50 μm×50 μm region of any cross section, the average value of the long diameter of the silicon nitride crystal particles is 0.1 μm or more and 10 μm or less, and the average value of the aspect ratio of the silicon nitride crystal particles is 1.5 or more and 10 or less. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a diagram showing an example of a cross-sectional structure of a silicon nitride sintered body according to an embodiment.
[0019] Figure 2 This is a diagram showing an example of a bearing ball according to an embodiment.
[0020] Figure 3 This is a diagram showing an example of a bearing according to an embodiment.
[0021] Figure 4 is an example of a first plot.
[0022] Figure 5 is an example of the second plot.
[0023] Figure 6 is an example of the third plot.
[0024] Figure 7 This is a diagram showing an example of the XRD peak of the silicon nitride sintered body according to the embodiment. DETAILED DESCRIPTION
[0025] The silicon nitride sintered body of the embodiment comprises silicon nitride crystal particles and grain boundary phases. In a 20 μm×20 μm region of any cross section, the average value of the amount of dissolved oxygen in the silicon nitride crystal particles is 0.2 wt% or more. In a 50 μm×50 μm region of any cross section, the average value of the long diameter of the silicon nitride crystal particles is 0.1 μm or more and 10 μm or less, and the average value of the aspect ratio of the silicon nitride crystal particles is 1.5 or more and 10 or less.
[0026] Figure 1 This is a diagram showing an example of a cross-sectional structure of a silicon nitride sintered body according to an embodiment.
[0027] Figure 1 In the figure, symbol 1 represents a silicon nitride sintered body, symbol 2 represents silicon nitride crystal particles, and symbol 3 represents a grain boundary phase. Figure 1 This is a schematic diagram showing an example of the cross-sectional structure of a silicon nitride sintered body.
[0028] The silicon nitride sintered body 1 comprises silicon nitride crystal particles 2 and grain boundary phases 3. The grain boundary phases 3 are distributed in the gaps between the silicon nitride crystal particles 2. The grain boundary phases 3 are formed by the reaction of the sintering aid described later. Due to the presence of the grain boundary phases 3, the silicon nitride crystal particles 2 are firmly bonded, and a silicon nitride sintered body with high strength can be formed. In addition, pores not shown in the figure may also exist in the silicon nitride sintered body.
[0029] The average value of the long diameter of the silicon nitride crystal particles 2 is greater than 0.1 μm and less than 10 μm. In addition, the average aspect ratio of the silicon nitride crystal particles 2 is greater than 1.5 and less than 10. For the determination of the average value of the long diameter and the average aspect ratio, a scanning electron microscope (SEM) photograph is used. A measurement area is set in an arbitrary cross section of the silicon nitride sintered body 1. The SEM photograph is taken at a magnification of 2000 times or more. In the SEM photograph, the maximum diameter of each silicon nitride crystal particle is measured. The maximum diameter of the silicon nitride crystal particles photographed in the SEM photograph is set as the long diameter. In the measurement area, the average value of the maximum diameter of the silicon nitride crystal particles photographed in the area of 50 μm×50 μm is set as the average value of the long diameter.
[0030] In the determination of the aspect ratio, the long diameter and the short diameter are used. The above-mentioned maximum diameter is set as the long diameter. For the silicon nitride crystal particle 2 that obtains the long diameter, the length of the line segment extending vertically from the center point of the long diameter is set as the short diameter. The aspect ratio is calculated by long diameter / short diameter. The second decimal place of the long diameter / short diameter is rounded off. Similar to the average value of the long diameter, the average value of each silicon nitride crystal particle photographed in an area of 50μm×50μm is set as the average aspect ratio. It should be noted that the long diameter and the short diameter are measured using the portion of the silicon nitride crystal particle photographed in the SEM photograph. For example, sometimes one silicon nitride crystal particle overlaps with other silicon nitride crystal particles, and the entire outline of the one silicon nitride crystal particle cannot be seen. In this case, only the visible portion (the portion photographed in the SEM photograph) is used to measure the long diameter and the short diameter of the one silicon nitride crystal particle. In addition, for silicon nitride crystalline particles whose contours are interrupted at the ends of the 50μm×50μm SEM photograph, only the visible portion (the portion photographed in the SEM photograph) is used to measure the major and minor diameters. In the case where it is difficult to confirm the contours of the silicon nitride crystalline particles in the SEM photograph, the measurement area can also be etched. By performing the etching process, the surface portion and the grain boundary phase of the silicon nitride crystalline particles are removed. As a result, it becomes easy to confirm the contours of the silicon nitride crystalline particles. In addition, in the presence of Sialon crystalline particles, the Sialon crystalline particles are counted as silicon nitride crystalline particles. The etching rate of silicon nitride crystalline particles is different from the etching rate of the grain boundary phase. Take the case where the etching rate of silicon nitride crystalline particles is faster than that of the grain boundary phase as an example. In this case, a portion of each silicon nitride crystalline particle 2 is removed to a greater extent than the grain boundary phase 3. As a result, the surface of the silicon nitride crystalline particle 2 is located below the surface of the grain boundary phase 3. Thus, the grain boundary phase 3 becomes three-dimensional like a wall relative to the silicon nitride crystal particle 2, so that the silicon nitride crystal particle 2 and the grain boundary phase 3 can be easily distinguished by contrast or the like.
[0031] The average value of the long diameter of the silicon nitride crystal particles 2 present in the region of 50μm×50μm is within the range of 0.1μm to 10μm. The average aspect ratio of the silicon nitride crystal particles 2 present in the region of 50μm×50μm is 1.5 to 10. If it is within this range, the durability of the silicon nitride sintered body 1 during high-speed rotation can be improved. In addition, it is also possible to seek to improve the mechanical strength of the silicon nitride sintered body 1. If the average value of the long diameter is less than 0.1μm, the silicon nitride crystal particles 2 may be too small and the durability may be reduced. If the average value of the long diameter exceeds 10μm, the mechanical strength of the silicon nitride sintered body 1 may be reduced. Therefore, the average value of the long diameter is preferably 0.1μm to 10μm, and further 0.5μm to 8μm.
[0032] If the average aspect ratio is less than 1.5, there are fewer elongated silicon nitride crystal particles, so the mechanical strength of the silicon nitride sintered body 1 may be reduced. If the average aspect ratio exceeds 10, the gap between the silicon nitride crystal particles 2 may become larger. If the gap between the silicon nitride crystal particles 2 becomes larger, the grain boundary phase 3 becomes larger. The large grain boundary phase 3 may cause the mechanical strength of the silicon nitride sintered body 1 to decrease. Therefore, the average aspect ratio is preferably greater than 1.5 and less than 10, and further greater than 2 and less than 10.
[0033] In any cross section, it is preferred that both silicon nitride crystal particles 2 having a long diameter of less than 3 μm and silicon nitride crystal particles 2 having a long diameter of 3 μm or more exist. Since the silicon nitride sintered body 1 includes small silicon nitride crystal particles 2 and large silicon nitride crystal particles 2, small crystal particles can be present in the gaps between large crystal particles. Thus, the durability and mechanical strength of the silicon nitride sintered body 1 can be improved.
[0034] In the silicon nitride sintered body 1, when the amount of dissolved oxygen in the silicon nitride crystal particles 2 present in the 20 μm×20 μm area of any cross section is measured, their average value is more than 0.2 wt%. For the determination of the amount of dissolved oxygen in the silicon nitride crystal particles 2, TEM-EDS is used. TEM is the abbreviation for transmission electron microscope. EDS is the abbreviation for energy dispersive X-ray spectrometer. The measurement method using TEM-EDS is also referred to as EDS analysis. The method for determining the amount of dissolved oxygen in silicon nitride crystal particles 2 using EDS analysis is shown in Japanese Patent Gazette No. 2022-71426 (Patent Document 3).
[0035] For the sample for EDS analysis, an arbitrary cross section of the silicon nitride sintered body 1 is used. The sample is collected from an arbitrary cross section by FIB (focused ion beam) processing or ion milling processing. The thickness of the sample is preferably in the range of 0.05 μm or more and 0.5 μm or less. In order to prevent surface oxidation of the sample, it is preferred to prepare and store the sample in a vacuum or in an inert gas atmosphere.
[0036] For EDS, use JEOL JED-2300T or an apparatus having equivalent or higher performance. For TEM, use JEOL JEM-200CX (accelerating voltage 200 kV) or an apparatus having equivalent or higher performance. In EDS analysis, the recommended conditions are an accelerating voltage of 200 kV, an irradiation current of 1.00 nA, and a spot diameter of 1 nm during analysis. The recommended analysis time is 30 seconds, and the sample tilt angle is X=10°, Y=0°. The exemplified measurement conditions can also be changed, but the above measurement conditions are used for the measurement used to obtain the first plot described later.
[0037] By using TEM-EDS, the silicon nitride crystal particle 2 can be selected as the analysis point. In order to measure the solid dissolved oxygen, there is a method using the secondary ion mass spectrometry (SIMS) method. As for the measurement using the SIMS method, only the solid dissolved oxygen content of the large silicon nitride crystal particle 2 can be measured. In addition, even the nano SIMS method that can reduce the irradiation diameter is difficult to identify the image of the silicon nitride crystal particle 2. Therefore, as for the measurement using the SIMS method, the solid dissolved oxygen content of the small silicon nitride crystal particle 2 cannot be measured.
[0038] As another method for measuring the amount of dissolved oxygen, there is a total dissolution method. In the total dissolution method, the grain boundary phase of the silicon nitride sintered body is dissolved and the silicon nitride crystal particles are taken out. The oxygen content of the taken out silicon nitride crystal particles is measured. However, it is difficult to completely dissolve and remove the grain boundary phase, and the measurement accuracy and reproducibility of the amount of dissolved oxygen are reduced due to the residual grain boundary phase.
[0039] Regarding TEM-EDS, by setting the analysis point diameter to 1 nm, it is possible to set the analysis point only for silicon nitride crystal particles 2. Furthermore, regardless of the size of silicon nitride crystal particles 2, the amount of dissolved oxygen in silicon nitride crystal particles 2 can be measured.
[0040] In the EDS analysis, at least 10 points are set as analysis points from all the silicon nitride crystal particles 2 present in the area of 20μm×20μm. The 10 analysis points are set on different silicon nitride crystal particles as much as possible. That is, it is preferred to select more than 10 silicon nitride crystal particles 2 as analysis points. Through EDS analysis, the atomic ratio of silicon (Si), oxygen (O), and nitrogen (N) is measured. Three or more locations where the Si count is greater than 300,000 cps and a total of more than 10 locations are selected as measurement locations. Among the selected multiple analysis points, if the number of locations where the Si count is greater than 300,000 cps is less than 3, reselect the analysis points until the number of locations where the Si count is greater than 300,000 cps is greater than 3. The Si count of more than 300,000 cps indicates a state in which the oxygen amount can be measured without being affected by surface oxygen. Therefore, even if the surface of the sample is naturally oxidized, the amount of dissolved oxygen can be measured.
[0041] Figure 4 is an example of a first plot. Figure 5 is an example of the second plot. Figure 6 is an example of the third plot. Figures 4 to 6 This is the result of measurement in Example 3 described later.
[0042] First, a first plot is prepared. In the first plot, the atomic ratio of oxygen element / silicon element is plotted against the Si count. In the first plot, the horizontal axis represents the Si count (cps) and the vertical axis represents the O / Si atomic ratio. Next, a second plot is prepared. In the second plot, the atomic ratio of nitrogen element / silicon element is plotted against the Si count.
[0043] Next, the atomic ratio of oxygen element / silicon element in the first plot is corrected using the second plot. In the case of silicon nitride sintered bodies, the absorption of X-rays generated by oxygen (O) as a light element is greater than the absorption of X-rays generated by silicon (Si). The absorption characteristics of oxygen (O) and nitrogen (N) are similar. In addition, the main phase of the silicon nitride sintered body is Si3N4. Therefore, the theoretical value of the N / Si atomic ratio is 4 / 3. The first plot is corrected by the approximate data of the atomic ratio of Si and N. In this correction method, the O / Si atomic ratio of the first plot is corrected using the N / Si atomic ratio of each measured point of the second plot. That is, the difference between the N / Si atomic ratio of each measured point and 4 / 3 (=1.33) as the theoretical value is used to correct the O / Si atomic ratio of the first plot. For example, when the N / Si atomic ratio is 0.70, the correction coefficient becomes 1.9 (=1.33 / 0.70). The correction value is calculated by the O / Si atomic ratio × correction coefficient. By this method, the O / Si atomic ratio in the first plot is corrected, and the corrected first plot is used as the third plot.
[0044] Next, when the slope of the approximate straight line at three or more points of the third plot is expressed as y=aX+b, the value of -4×10 -8 ≤a≤4×10 -8 The convergence area. In the third plot, the horizontal axis represents the Si count number (cps), and the vertical axis represents the corrected O / Si atomic ratio. Regarding the slope of the approximate straight line y=aX+b, X is the horizontal axis, y is the vertical axis, a is the slope, and b is the point of contact with the vertical axis (y axis). In the calculation of the approximate straight line, the approximation function of the accumulation software is used. As the accumulation software, Microsoft Excel (registered trademark) can be used.
[0045] The slope a of the approximate straight line of the third plot is within the above range. The convergence area is the area where the influence of natural oxidation and grain boundary phase on the sample surface is minimized. When the measurement result is affected by natural oxidation or grain boundary phase on the sample surface, the unevenness of the O / Si atomic ratio also increases. Therefore, the slope a is not within the above range. The slope a of the approximate straight line is -4×10 -8 Above and 4×10 -8The following range indicates that the variation of the O / Si atomic ratio is reduced. Since the variation of the O / Si atomic ratio is reduced, it is known that the value is a value that sufficiently reduces the influence of natural oxidation and grain boundary phase. Therefore, the value included in the convergence region becomes to indicate the amount of solid solution oxygen.
[0046] After the convergence region is found, the average value of the O / Si atomic ratio from the side with a large Si count to the third point is calculated among the values contained in the convergence region. The average value of the O / Si atomic ratio from the side with a large Si count to the third point is the region where the influence of natural oxidation or the second phase at the grain boundary is further reduced. The amount of dissolved oxygen is calculated using the calculated average value of the O / Si atomic ratio. Figure 6 In the third plot, the slope a of the approximate straight line with more than three points is -4×10 -8 Above and 4×10 -8 The convergence region within the following range is a region where the Si count number is 350,000 or more.
[0047] Since silicon nitride crystal particles are Si3N4, the dissolved oxygen content (wt%) can be calculated by (3 / 7)×(average value of O / Si atomic ratio). This is a method for calculating the dissolved oxygen content based on the amount of oxygen corresponding to the amount of Si in the Si3N4 crystal particles. In addition, as mentioned above, the slope a of the approximate straight line with more than three points becomes -4×10 -8 Above and 4×10 -8 The convergence area within the following range is obtained by the measurement results of the analysis points where the Si counts are obtained to be more than 300,000 cps. The analysis points with more Si counts are the points where the oxidation of the sample surface and the influence of the grain boundary phase are minimized. As far as EDS analysis is concerned, it is not possible to selectively measure only the area above 300,000 cps. Therefore, regardless of the number of counts, the method of measuring more than 10 places by EDS analysis is effective. Extract the analysis points with Si counts of more than 300,000 cps from the more than 10 analysis points measured. When the number of analysis points with Si counts of more than 300,000 cps is less than 3 locations, perform EDS analysis on the new analysis points until the number of analysis points with Si counts of more than 300,000 cps becomes more than 3 locations.
[0048] The amount of dissolved oxygen in the silicon nitride sintered body of the embodiment measured by the above method is 0.2wt% or more. The amount of dissolved oxygen measured by TEM-EDS is an average value corresponding to the number of measurement points. That is, the average value of the amount of dissolved oxygen in the silicon nitride crystal particles present in the 20μm×20μm area of any cross section is 0.2wt% or more. The so-called arbitrary cross-sectional structure means that no matter which cross section the amount of dissolved oxygen in the silicon nitride crystal particles present in the 20μm×20μm area is measured, their average value is 0.2wt% or more.
[0049] As for the silicon nitride sintered body in which the dissolved oxygen content of silicon nitride crystal particles is controlled as described above, the durability under high-speed and high-load conditions is improved. It should be noted that if the dissolved oxygen content becomes 0.2wt% or more, the thermal conductivity becomes 70W / m·K or less, and further 40W / m·K or less. In addition, the dissolved oxygen content of all silicon nitride crystal particles present in the above-mentioned 20μm×20μm area is preferably in the range of 0.2wt% or more and 1.5wt% or less. As described above, the TEM-EDS method can be used to set only silicon nitride crystal particles as analysis points. By controlling the dissolved oxygen content of all silicon nitride crystal particles, the performance can be further improved. It should be noted that when measuring the dissolved oxygen content of all silicon nitride crystal particles, an analysis point is set at least one of the silicon nitride crystal particles present in the 20μm×20μm area. The analysis method is as described above. The solid dissolved oxygen content of 0.2wt% or more and 1.5wt% or less based on the analysis point set for each silicon nitride crystal particle indicates that the solid dissolved oxygen content of each silicon nitride crystal particle is controlled. In addition, if the solid dissolved oxygen content exceeds 1.5wt%, it may become impossible to effectively utilize the characteristics of the silicon nitride crystal particles. Therefore, the solid dissolved oxygen content is preferably 0.2wt% or more and 1.5wt% or less, and further 0.3wt% or more and 1.3wt% or less.
[0050] By controlling the amount of dissolved oxygen in the silicon nitride crystal particles, the durability of each silicon nitride crystal particle can be improved. In addition, the dissolved oxygen can be any of substitutional and intrusive types. At least a portion of the dissolved oxygen is preferably substitutional. The substitutional type means that a portion of the elements constituting the crystal lattice is replaced by a dissolved element. That is, the substitutional type is a state in which a portion of the crystal lattice of the silicon nitride crystal particle is replaced by oxygen. By the presence of substitutional dissolved oxygen, the deformation of the silicon nitride crystal lattice can be suppressed.
[0051] As described below, the silicon nitride sintered body of the embodiment can be used for bearing balls. If the bearing balls slide, loads and frictional heat are generated. Even if loads and frictional heat are generated, the deformation of the silicon nitride crystal lattice can be suppressed. In addition, when the silicon nitride crystal particles contain dissolved oxygen, the adhesion between the silicon nitride crystal particles and the grain boundary phase can be improved. By utilizing the reaction of the dissolved oxygen of the silicon nitride crystal particles with the sintering aid to form a part of the grain boundary phase, the adhesion can be improved. Thus, the durability when loads and frictional heat are generated can also be improved.
[0052] In the above-mentioned 20μm×20μm area, the difference between the amount of dissolved oxygen of silicon nitride crystal particles with a long diameter less than 3μm and the amount of dissolved oxygen of silicon nitride crystal particles with a long diameter of 3μm or more is preferably 0.1wt% or less. In other words, in the 20μm×20μm area, when the average value of the amount of dissolved oxygen obtained by setting only silicon nitride crystal particles with a long diameter less than 3μm as analysis points is set as the amount of dissolved oxygen A, and the average value of the amount of dissolved oxygen obtained by setting only silicon nitride crystal particles with a long diameter of 3μm or more as analysis points is set as the amount of dissolved oxygen B, |solid dissolved oxygen amount A-solid dissolved oxygen amount B| is preferably 0.1wt% or less. In this way, by the presence of small silicon nitride crystal particles and large silicon nitride crystal particles, it is possible to seek improvements in durability and mechanical strength.
[0053] The silicon nitride sintered body 1 preferably contains a grain boundary phase 3 of more than 1 mass % and less than 20 mass %. The grain boundary phase 3 is formed by the reaction of sintering aids with each other or the reaction of sintering aids with impurity oxygen on the surface of silicon nitride powder. The grain boundary phase 3 has the effect of firmly combining silicon nitride crystal particles with each other or suppressing the generation of pores. By controlling the amount of the grain boundary phase 3, the mechanical, electrical and thermal properties can be improved. When the grain boundary phase 3 is less than 1 mass %, the proportion of the grain boundary phase 3 is small. If the grain boundary phase 3 is small, pores are easily generated. In addition, if the grain boundary phase 3 exceeds 20 mass %, although the generation of pores can be suppressed, the mechanical strength is easily reduced. Therefore, the content of the grain boundary phase 3 is preferably more than 1 mass % and less than 20 mass %, and further more than 3 mass % and less than 15 mass %. In addition, by setting the porosity of the silicon nitride sintered body 1 to less than 2% and the pore size to less than 5μm, the flexural strength of the silicon nitride sintered body 1 can be set to more than 700MPa, and further more than 900MPa. In addition, as electrical properties, the effect of suppressing charging can be listed. As thermal properties, the effect of suppressing thermal expansion can be listed. For example, when the silicon nitride sintered body 1 is used for bearing balls, if the charging can be suppressed, the generation of electrolytic corrosion can be suppressed. In addition, the suppression of thermal expansion can suppress the change in the gap between the inner ring and the outer ring when the silicon nitride sintered body 1 is used for the bearing. The pore size is set to the maximum diameter of the pores taken in the SEM photograph of 50μm×50μm. In addition, the total area of the pores taken in the measurement area of 50μm×50μm is calculated. This operation is performed at any 3 places, and the average value of the total area of the pores is set as the porosity (%). It should be noted that, when the porosity of silicon nitride sintered body 1 is 2% or less, the mass of grain boundary phase 3 may be set to a value obtained by subtracting the total mass of silicon nitride crystal particles 2 from 100 mass %.
[0054] The grain boundary phase 3 preferably contains one or more selected from rare earth elements, aluminum, magnesium, titanium, hafnium, tungsten, molybdenum, and silicon. Rare earth elements are yttrium, lanthanide elements, etc. For example, as rare earth elements, one or more selected from yttrium (Y), erbium (Er), ytterbium (Yb), and cerium (Ce) can be listed. These elements are added as sintering aids. As sintering aids, one or more selected from metal oxides, metal nitrides, metal carbides, and metal sulfides can be used. It should be noted that if the grain boundary phase 3 is within the range of 1% by mass or more and 20% by mass or less, other components can also be added as sintering aids.
[0055] When an X-ray diffraction (XRD) analysis is performed on an arbitrary cross section of the silicon nitride sintered body 1, the strongest peak intensity detected at 42.4±0.3° is set as I 42.4° The strongest peak intensities detected at 27.1±0.3°, 33.6±0.3°, and 36.1±0.3° corresponding to β-Si3N4 crystals were set as I 27.1° ,I 33.6° ,I 36.1° . (I 42.4° ) / (I 27.1° +I 33.6° +I 36.1° ) is preferably greater than or equal to 0.005 and less than or equal to 0.030.
[0056] For XRD analysis, use D8 ADVANCE made by BRUKER or an apparatus having equivalent or higher performance. The grinding surface with a surface roughness Ra of less than 1 μm is used as the measurement surface for XRD analysis. XRD analysis is carried out under the measurement conditions of Cu target (Cu-Kα), tube voltage 40 kV, tube current 40 mA, scanning speed 2.0° / min, slit (RS) 0.15 mm, and scanning range (2θ) 10° to 60°. In addition, the so-called strongest peak is the largest peak within a specified range. The so-called strongest peak intensity is the diffraction intensity at the peak top of the largest peak. The peak position of XRD analysis is determined by the material and crystallization state of the crystalline phase. In addition, the peak ratio corresponds to the existence ratio of each crystalline phase.
[0057] I 42.4° It is a peak that does not appear in β-Si3N4 crystals. Therefore, I 42.4° The peak is based on the crystalline phase contained in the grain boundary phase. By making the grain boundary phase 3 around the silicon nitride crystal particle 2 with controlled dissolved oxygen content contain a crystalline phase, the grain boundary is strengthened and the durability can be improved. Therefore, it is preferred to satisfy 0.005≤(I 42.4° ) / (I 27.1° +I 33.6° +I 36.1° )≤0.030. It should be noted that I42.4° This can be controlled by allowing at least one selected from rare earth elements and aluminum to exist in the grain boundary phase 3. In other words, allowing a rare earth element-aluminum-oxygen system crystalline compound pair I to exist in the grain boundary phase 3 42.4° The control is effective.
[0058] Figure 7 : is a diagram showing an example of XRD peaks of a silicon nitride sintered body according to an embodiment. Specifically, Figure 7 The results of XRD analysis of the silicon nitride sintered body of Example 3 described later are shown. Figure 7 , the results of extracting only the scanning range of 20° to 50° from the analysis results obtained by the XRD analysis using the above-mentioned measurement conditions are shown. Figure 7 In the figure, the horizontal axis represents the diffraction angle (2θ), and the vertical axis represents the diffraction intensity. In the example shown in the figure, peaks P1 to P4 appear at 27.1±0.3°, 33.6±0.3°, 36.1±0.3°, and 42.4±0.3°, respectively. 27.1° ,I 33.6° ,I 36.1° , and I 42.4° are the intensities at the apex of peaks P1 to P4 respectively. 42.4° ) / (I 27.1° +I 33.6° +I 36.1° ) is 0.008, which is within the range of 0.005 to 0.030. Figure 7 In the example shown in , peaks P5 to P9 appear in addition to these. These peaks are caused by the grain boundary phase 3 and the like, and can further improve the durability of the silicon nitride sintered body 1. The silicon nitride sintered body 1 of the embodiment is not particularly limited to the presence or absence of peaks other than the peaks P1 to P4.
[0059] The silicon nitride sintered body 1 has high strength and excellent wear resistance. The three-point bending strength can be set to 700 MPa or more, and further 900 MPa or more. The fracture toughness value can be set to 6 MPa·m 1 / 2 Above, further 7MPa·m 1 / 2or more. In addition, the Vickers hardness HV1 can be set to 1400 or more. It should be noted that the three-point bending strength can be measured by a method based on JIS-R-1601 (2008). JIS-R-1601 corresponds to ISO 14704. Fracture toughness can be measured using the new original formula according to the IF method of JIS-R-1607 (2015). JIS-R-1607 corresponds to ISO15732. Vickers hardness can be measured according to JIS-R-1610 (2003) with a test force of 9.807N HV1. Wear resistance is durability during high-speed rotation. JIS-R-1610 corresponds to ISO 14705.
[0060] The silicon nitride sintered body 1 of the embodiment can be used for a wear-resistant member. The wear-resistant member is preferably one selected from a bearing ball, a roller, a roll, and a tool member for friction stir welding.
[0061] Figure 2 This is a diagram showing an example of a bearing ball as a type of wear-resistant member. Figure 3 This is a diagram showing an example of a bearing in which bearing balls are incorporated. Figure 2 and Figure 3 In the figure, symbol 4 is the bearing ball, symbol 5 is the inner ring, symbol 6 is the outer ring, and symbol 10 is the bearing.
[0062] The bearing balls 4 are obtained by processing the silicon nitride sintered body 1 into a spherical shape. The bearing 10 has a structure in which a plurality of bearing balls 4 are interposed between an inner ring 5 and an outer ring 6. The number of bearing balls 4 used in the bearing 10 is arbitrary.
[0063] The bearing ball 4 is spherical in shape. The bearing ball 4 is ground as required so that the surface roughness Ra becomes less than 0.1 μm. Regarding the bearing ball 4, the surface roughness Ra corresponding to the grade is specified in ASTM F2094 of the American Society for Testing and Materials. Therefore, the bearing ball 4 is ground so that the surface roughness becomes corresponding to the grade. In addition, even in the case where the silicon nitride sintered body 1 is applied to a wear-resistant component other than a bearing ball, surface grinding is performed as required. In other words, the wear-resistant component of the embodiment preferably has a ground surface with a surface roughness Ra of less than 0.1 μm, and further Ra of less than 0.02 μm.
[0064] A roller is a cylindrical bearing ball. A roller is a cylindrical component. Rollers are used as conveying rollers, rolling rollers, etc. In addition, the silicon nitride sintered body 1 can also be used for a friction stir welding tool component. The friction stir welding tool component is a component called a probe. For example, a probe is shown in the international publication WO2016 / 047376 (Patent Document 4). Bearing balls, rollers, rollers, and friction stir welding tool components all have sliding surfaces. These components are wear-resistant components that make surface contact with the object component.
[0065] In the bearing 10, a plurality of bearing balls 4 are arranged between the inner ring 5 and the outer ring 6. The bearing 10 is fixed to a rotating shaft (not shown). If the rotating shaft is rotated, a load is applied to the bearing 10. The loads applied to the bearing 10 include radial load, thrust load, and moment load. The radial load is a load applied in a direction perpendicular to the rotating shaft (circumferential direction of the rotating shaft). The thrust load is a load applied in a direction parallel to the rotating shaft (axial direction of the rotating shaft). The moment load is a load generated by the eccentricity of the rotating shaft.
[0066] If the bearing 10 is rotated, the bearing ball 4 slides while contacting the inner ring 5 and the outer ring 6. In the bearing ball 4 of the embodiment, the amount of dissolved oxygen in the silicon nitride crystal particles 2 is controlled. Therefore, the bearing ball 4 has excellent durability against contact. If high-speed rotation is performed, the radial load and thrust load become larger. In addition, bearing steels such as SUJ2 are sometimes used for the inner ring 5 and the outer ring 6. In the past, bearing steels were sometimes used for bearing balls. The bearing ball 4 of the embodiment is composed of silicon nitride. The specific gravity of silicon nitride is smaller than that of steel, and the aggressiveness of the bearing ball 4 to the inner ring 5 and the outer ring 6 can be reduced. That is, it is possible to suppress the sliding surface of the track ring from being cut away due to the sliding from the bearing ball 4. If the sliding surface is cut away, eccentricity of the rotating shaft occurs. By reducing the aggressiveness, the eccentricity of the rotating shaft can be suppressed. Therefore, according to the embodiment, it is also possible to suppress the increase of the moment load. For example, the higher the speed of rotation, the greater the difference in centrifugal force. Furthermore, according to the embodiment, there is also an effect of suppressing a temperature rise due to rotational friction.
[0067] Each load is affected by the weight, that is, the volume, of the bearing ball. For small bearing balls with a diameter of less than 3 mm, even if the rotation speed increases, the effect on the load is small. On the other hand, if the diameter of the bearing ball becomes 5 / 16 inch (7.9375 mm) or more, the effect on the load is greatly apparent. The bearing 10 has a plurality of bearing balls 4. According to the embodiment, the durability of the bearing balls 4 can be improved. In addition, the aggressiveness to the object component can also be reduced. The aggressiveness to the object component generated by each bearing ball 4 is reduced. Therefore, the durability of the bearing 10 using the bearing balls 4 of the embodiment can also be improved. In addition, the bearings mounted in automobiles, working machinery, etc. are used in a vibrating environment. In a vibrating environment, the aggressiveness to the object component becomes higher. The bearing 10 using the bearing balls 4 of the embodiment shows excellent durability even when used in a vibrating environment.
[0068] Next, a method for producing the silicon nitride sintered body 1 of the embodiment will be described. The method for producing the silicon nitride sintered body 1 of the embodiment is not particularly limited as long as it has the above-mentioned configuration. Here, a method for obtaining the silicon nitride sintered body 1 with a high yield will be described.
[0069] First, prepare silicon nitride powder. Preferably, the average particle size of the silicon nitride powder is less than 2.5 μm, and the impurity oxygen content is less than 2 mass%. If the impurity oxygen content exceeds 2 mass%, it may become difficult to control the amount of dissolved oxygen. In addition, it is preferred to use silicon nitride powder with an alpha conversion rate of 90% or more. The α-type silicon nitride powder is grown into β-type silicon nitride crystalline particles through a sintering process. β-type silicon nitride crystalline particles tend to become elongated particles with an aspect ratio of more than 1.5. By complexly distributing the elongated particles, the mechanical properties of the silicon nitride sintered body 1 can be improved.
[0070] As silicon nitride powder, there is silicon nitride powder produced by an imide decomposition method, a direct nitridation method, etc. Silicon nitride powder produced by an imide decomposition method is sometimes referred to as imide powder. Silicon nitride powder produced by a direct nitridation method is sometimes referred to as direct nitridation powder. Regarding imide powder, the amount of oxygen in the particles is small and the amount of impurities is also small. As for direct nitridation powder, the amount of oxygen and impurities in the particles are large compared to imide powder. As long as the amount of impurity oxygen is less than 2% by mass, either imide powder or direct nitridation powder can be used.
[0071] Next, a sintering aid powder is prepared. The sintering aid powder is preferably a metal compound powder of one or more selected from rare earth elements, aluminum, magnesium, titanium, hafnium, tungsten, molybdenum, and silicon. The metal compound powder is one or more selected from metal oxides, metal nitrides, metal carbides, and metal sulfides.
[0072] Rare earth compound powder and aluminum compound powder can react with each other to form grain boundary phase 3. Rare earth elements are preferably selected from one or more of yttrium (Y), erbium (Er), ytterbium (Yb), and cerium (Ce). By adding rare earth elements in the form of rare earth oxides, rare earth elements and aluminum compounds become easy to react. In addition, the aluminum compound is preferably selected from one or two of aluminum oxide, aluminum nitride, and MgO·Al2O3 spinel. They can react with rare earth oxides to form rare earth aluminum oxides, or rare earth aluminum nitrides, and rare earth aluminum oxynitrides. Rare earth aluminum oxides, rare earth aluminum nitrides, and rare earth aluminum oxynitrides are collectively referred to as rare earth aluminum compounds. Rare earth aluminum compounds may also contain other elements. As other elements, magnesium, hafnium, and silicon can be listed.
[0073] One or more selected from titanium, hafnium, tungsten, molybdenum, and silicon have the effect of strengthening the grain boundary phase. For example, titanium oxide (TiO2) is converted into titanium nitride (TiN) through a sintering process. Titanium nitride particles become strengthening particles that strengthen the grain boundary phase. In addition, molybdenum nitrides, carbides, and sulfides also become strengthening particles. Silicon carbides also become strengthening particles. By dispersing strengthening particles in the grain boundary phase 3 formed by the rare earth aluminum compound to strengthen the grain boundary phase 3, wear resistance can be further improved.
[0074] When the total amount of silicon nitride powder and sintering aid powder is set to 100 parts by mass, the sintering aid powder is preferably in the range of 1 part by mass or more and 20 parts by mass or less. The grain boundary phase 3 is formed by the reaction between the sintering aids or the reaction between silicon nitride and the sintering aid. By controlling the amount of sintering aid powder added, the mass ratio of the grain boundary phase 3 can be controlled.
[0075] Next, a process of mixing silicon nitride powder with sintering aid powder is performed. In order to control the major diameter and aspect ratio of the silicon nitride crystal particles in the silicon nitride sintered body, sintering homogeneity is required. Therefore, the silicon nitride powder and the sintering aid powder must be mixed evenly. In the sintering process, the sintering aid reacts to form a grain boundary phase 3. The growth reaction of the silicon nitride crystal particles 2 is carried out through the grain boundary phase 3. By uniformly mixing the silicon nitride powder and the sintering aid powder, the reaction through the grain boundary phase 3 can be homogenized. That is, the homogeneity of sintering property indicates the homogeneity of the reaction of the sintering aid to form a grain boundary phase and the homogeneity of the grain growth of the silicon nitride crystal particles.
[0076] In addition, a ball mill or a bead mill is used in the mixing process. Silicon nitride powder and sintering aid powder mostly exist as agglomerated secondary particles. These secondary particles will become an obstacle to homogeneous sintering properties. By uniformly mixing the secondary particles while breaking them into non-agglomerated primary particles, the homogeneity of sintering properties can be improved.
[0077] In the mixing process accompanying the disintegration, it is preferred not to apply such strong stress that further destroys the primary particles. If the primary particles are destroyed, a fracture surface is formed in the silicon nitride powder. Since the fracture surface is an active surface, a surface different from the original reactivity of the primary particles is formed. This will become an obstacle to homogeneous sintering. Therefore, it is effective to suppress the formation of fracture surfaces in primary particles. By suppressing the formation of fracture surfaces, the reaction of silicon nitride powder with oxygen can be suppressed. As a result, the amount of dissolved oxygen in the formed silicon nitride crystalline particles can be controlled within the range of more than 0.2wt% and less than 1.5wt%.
[0078] For the above-mentioned secondary particle disintegration, wet disintegration using a solvent is suitable. A solvent with high wettability to the particle surface and low reactivity with the particles is used. According to this method, the stress required for disintegration is small, and the destruction of the primary particles can be suppressed. For the mixing accompanying the disintegration of silicon nitride powder and sintering aid powder, an organic solvent is suitable. For the organic solvent, alcohols, ketones, or aromatics are suitable. An organic solvent obtained by mixing two or more selected from alcohols, ketones, and aromatics can also be used. Alcohols are a general term for substances obtained by replacing part of the hydrogen of hydrocarbons with hydroxyl groups (OH groups). Ketones are substances represented by RC(=O)-R'. R and R' are alkyl groups, etc. Aromatics are organic substances containing benzene rings. These organic solvents have high wettability with silicon nitride powder and sintering aid powder. In addition, the reactivity of organic solvents with powders is low. As a result, silicon nitride powder and sintering aid powder can be evenly mixed.
[0079] When the crushing process is performed by a ball mill, the diameter of the medium is preferably less than 20 mm, and further less than 12 mm. The medium is a ceramic ball. A ball mill is a method in which powder and a medium are placed in a cylindrical container and the cylindrical container is rotated while the crushing is performed. The ball milling process using an organic solvent as described above is a wet crushing and mixing. By selecting an organic solvent suitable for the powder, the stress required for crushing can be reduced. That is, the secondary particles can be crushed with ceramic balls having a small diameter of the medium, which has the effect of reducing the energy of the medium colliding with the powder. By reducing the energy of the medium colliding with the powder, the formation of a fracture surface in the primary particle can be suppressed. It should be noted that the minimum value of the diameter of the medium is preferably greater than 3 mm. If the medium is too small, the operating efficiency may be reduced.
[0080] The time of wet crushing and mixing using a ball mill is preferably within the range of more than 5 hours and less than 40 hours. When the time of wet crushing and mixing is less than 5 hours, the effect of crushing may be insufficient, and many secondary particles may remain. If the time of wet crushing and mixing is longer than 40 hours, the possibility of forming a fracture surface in the primary particle increases. Therefore, the time of wet crushing and mixing using a ball mill is preferably within the range of more than 5 hours and less than 40 hours, and further within the range of more than 10 hours and less than 30 hours. In addition, in the ball milling process, the rotation speed of the cylindrical container is preferably within the range of more than 30 rpm and less than 500 rpm. It is further preferred that the rotation speed is within the range of more than 50 rpm and less than 180 rpm.
[0081] The fragmentation of secondary particles can be understood by investigating the particle size distribution before and after the fragmentation. As the secondary particles are fragmented, the number of primary particles increases, and the peak position of the particle size distribution (frequency distribution) shifts to the side with smaller particle sizes. In addition, the peak of the particle size distribution becomes more sharp.
[0082] The suppression of the formation of the fracture surface of the primary particles can be understood by measuring the oxygen content before and after the crushing. The oxygen content before the crushing is the oxygen content of the raw material powder. As long as the oxygen content of the raw material powder after the crushing does not increase significantly compared to before the crushing, there is no problem.
[0083] When the secondary particles are broken down into primary particles, a process of adsorbing a silane coupling agent on the surface of the primary particles may also be performed. If the silane coupling agent is adsorbed on the surface of the primary particles, the dispersibility in the solvent is improved, which is effective for uniform mixing. If the silane coupling agent is adsorbed, an oxide film is formed on the surface of the primary particles. Thus, the amount of oxygen on the surface of each primary particle can be more strictly controlled. As a result, the homogeneity of sinterability can be improved.
[0084] If silicon nitride powder is mixed with sintering aid powder and a solvent, a binder, etc. are added, a raw powder slurry can be obtained. Then, the obtained raw material slurry is used to perform a molding process. In the molding process, granulation is performed as needed to prepare a molded body. As molding processes, mold pressing, cold isostatic pressing (CIP), etc. can be listed. The molding pressure is preferably above 100 MPa.
[0085] Next, a degreasing step is performed to degrease the molded body. The degreasing step is preferably performed at a temperature in the range of 300° C. to 700° C. The degreasing step is performed in air or in a non-oxidizing atmosphere. The atmosphere of the degreasing step is not particularly limited.
[0086] Next, a sintering step is performed to sinter the degreased body. The sintering step is preferably performed in a range of 1600° C. to 1900° C. The sintering step may be any of normal pressure sintering and pressure sintering. The sintering step is preferably performed in a non-oxidizing atmosphere. Examples of the non-oxidizing atmosphere include a nitrogen atmosphere and an argon atmosphere.
[0087] During the sintering process, it is preferred to start pressurizing from 1500°C while heating to a range of 1600°C to 1900°C. When the temperature is below 1500°C, it is set to normal pressure (0.1MPa). The pressure at above 1500°C is preferably above 0.2MPa. In addition, it is preferred to control the heating rate from 1500°C to the sintering temperature within a range of 20°C / hr to 100°C / hr. Starting from around 1500°C, the α-type silicon nitride powder transforms into β-type and grain growth occurs. During the β-type transformation, oxygen in the silicon nitride crystal particles is easily released. By applying pressure, oxygen can be prevented from being excessively released from the silicon nitride crystal particles. It should be noted that the upper limit of the pressure is not particularly limited, but is preferably below 10MPa. In addition, control of the heating rate is effective in homogenizing the degree of grain growth.
[0088] The obtained sintered body is subjected to a hot isostatic pressing (HIP) process as required. The HIP process is preferably performed at a temperature in the range of 1500° C. to 1900° C. In the HIP process, a pressure of 30 MPa or more is preferably applied in a non-oxidizing atmosphere.
[0089] The silicon nitride sintered body 1 of the embodiment can be manufactured through the above steps. A wear-resistant member can be obtained by grinding the portion that becomes the sliding surface of the silicon nitride sintered body 1. The surface roughness Ra of the portion that becomes the sliding surface is preferably 1 μm or less.
[0090] (Example)
[0091] (Examples 1 to 5, Comparative Examples 1 to 2)
[0092] Prepare silicon nitride powder with an average particle size of 2.5 μm or less, an impurity oxygen content of 2 mass % or less, and an alpha conversion rate of 90% or more. Next, prepare a sintering aid. The composition of the sintering aid, the ratio of the silicon nitride powder, and the ratio of the sintering aid are as shown in Table 1.
[0093] Table 1
[0094]
[0095] Next, a mixing process is performed using a ball mill to mix the silicon nitride powder and the sintering aid. In the mixing process using the ball mill, one or more selected from alcohols, ketones, and aromatics are used as the organic solvent. The medium diameter, rotation speed, and mixing time are as described in Table 2. In Examples 3 and 5, a silane coupling agent is added during the mixing process.
[0096] Table 2
[0097]
[0098] The raw material slurry was prepared by a mixing process using a ball mill. Then, the obtained raw material slurry was spray granulated. The granulated powder was used to form a molded body by die pressing. Furthermore, a molded body was prepared by cold isostatic pressing. The molding pressure was set to 150 MPa.
[0099] Next, the compact is degreased. The degreasing step is performed at 300°C to 700°C in a non-oxidizing atmosphere. The degreased compact is sintered. In the sintering step, the pressure and the heating rate from 1500°C to the sintering temperature are as shown in Table 3. The sintering step is performed in a non-oxidizing atmosphere.
[0100] Table 3
[0101]
[0102] The obtained silicon nitride sintered body is subjected to HIP treatment. The HIP treatment is performed at a temperature of 1600° C. to 1800° C. and a pressure of 30 MPa to 150 MPa.
[0103] The silicon nitride sintered bodies of Examples and Comparative Examples were manufactured through the above sintering steps. The amount of dissolved oxygen in silicon nitride crystal particles contained in the silicon nitride sintered bodies, the average value of the major diameter of the silicon nitride crystal particles, the average aspect ratio, and the XRD peak were measured.
[0104] In the determination of the dissolved oxygen content of silicon nitride crystal particles, a 20 μm×20 μm area of an arbitrary cross section is set as the measurement area. Use TEM-EDS to measure each dissolved oxygen content. In addition, calculate the average value of the measured dissolved oxygen content. The measurement conditions of TEM-EDS are as described above. Set to the average value (A) of the dissolved oxygen content of silicon nitride crystal particles with a long diameter less than 3 μm, and the average value (B) of the dissolved oxygen content of silicon nitride crystal particles with a long diameter of more than 3 μm, and calculate the difference by |(A)-(B)|.
[0105] In addition, in the determination of the average value of the long diameter and the average aspect ratio of the silicon nitride crystal particles, a 50 μm×50 μm area of an arbitrary cross section is set as the measurement area. The average value of the long diameter and the average aspect ratio are determined using SEM photographs. The method of using SEM photographs is as described above. Furthermore, by XRD analysis, the intensity ratio (I 42.4° ) / (I 27.1° +I 33.6° +I 36.1° The conditions for XRD analysis were as described above.
[0106] It should be noted that, as mentioned above, Figures 4 to 6 The first plot, the second plot, and the third plot are respectively shown when the silicon nitride sintered body of Example 3 is measured. Figure 7 An example of the XRD peak of the silicon nitride sintered body of Example 3 is shown.
[0107] For each of Examples 1 to 5 and Comparative Examples 1 to 2, the average value of the dissolved oxygen content (wt%), the range of the values of each dissolved oxygen content, the average value (A), the average value (B), and the difference |(A)-(B)| are recorded in Table 4. The average value of the major axis, the average aspect ratio, the maximum value of the major axis, and the peak intensity ratio are recorded in Table 5.
[0108] Table 4
[0109]
[0110] Table 5
[0111]
[0112] As can be seen from Tables 4 and 5, in the silicon nitride substrate of the embodiment, the amount of dissolved oxygen is 0.2 wt% or more. In contrast, in Comparative Example 1, the amount of dissolved oxygen is as low as less than 0.2 wt%. In addition, the amount of dissolved oxygen in Comparative Example 2 is 0.2 wt% or more. However, the average value of the major diameter is outside the range of 0.1 μm or more and 10 μm or less, and the average aspect ratio is outside the range of 1.5 or more and 10 or less.
[0113] Next, the three-point bending strength, fracture toughness value, and Vickers hardness of each silicon nitride sintered body were measured. The three-point bending strength was measured by the method according to JIS-R-1601 (2008). The fracture toughness was measured using the new original formula according to the IF method of JIS-R-1607 (2015). The Vickers hardness was measured according to JIS-R-1610 (2003) with a test force of 9.807N HV1. These measurement results are recorded in Table 6.
[0114] Table 6
[0115]
[0116] In the examples and comparative examples, the three-point bending strength is 700 MPa or more, and the fracture toughness is 6 MPa·m 1 / 2 The Vickers hardness HV1 was 1400 or more. In addition, the thermal conductivity was measured and the result was 40 W / m·K or less.
[0117] Next, a wear resistance test was performed. For the sample, a bearing ball with a diameter of 3 / 8 inch (9.525 mm) was used. A bearing ball with a surface roughness Ra ground to 0.01 μm was prepared. In the wear resistance test, a thrust type rolling wear tester was used. A plate-like component made of bearing steel SUJ2 was prepared. The bearing ball was arranged on the plate-like component, and the wear resistance test was performed under the test conditions described in Table 7.
[0118] Table 7
[0119]
[0120] Three bearing balls are configured for one test. Nine bearing balls of the embodiment and the comparative example are tested respectively. If no cracks or notches are generated on the surface of any bearing ball, the test result is set as "OK". If cracks or notches are generated on the surface of even one bearing ball, the test result is set as "NG". These results are recorded in Table 8.
[0121] Table 8
[0122]
[0123] Furthermore, a sample having a diameter of 1-3 / 16 inch (30.16 mm) was prepared and subjected to the same wear resistance test. The results are shown in Table 9.
[0124] Table 9
[0125]
[0126] As can be seen from Tables 8 and 9, the bearing balls of the embodiment and the comparative example showed equivalent performance under test condition 1. In addition, the bearing balls of the embodiment showed excellent characteristics even under test condition 2. In particular, even for large balls such as 1-3 / 16 inches, the bearing balls of the embodiment showed excellent durability. In contrast, the performance of the bearing balls of the comparative example decreased under test condition 2. Therefore, it was found that controlling the amount of dissolved oxygen, etc., is an effective method to improve durability relative to load.
[0127] The embodiments of the present invention include the following configurations.
[0128] (Note 1)
[0129] A silicon nitride sintered body comprising silicon nitride crystal particles and a grain boundary phase.
[0130] In a 20 μm×20 μm region of an arbitrary cross section, the average value of the amount of dissolved oxygen in the silicon nitride crystal particles is 0.2 wt % or more.
[0131] In a 50 μm×50 μm region of an arbitrary cross section, the average value of the major diameter of the silicon nitride crystal particles is 0.1 μm to 10 μm, and the average value of the aspect ratio of the silicon nitride crystal particles is 1.5 to 10.
[0132] (Note 2)
[0133] The silicon nitride sintered body according to Supplementary Note 1, wherein the amount of dissolved oxygen in each of the silicon nitride crystal particles present in the region of 20 μm×20 μm is 0.2 wt% or more and 1.5 wt% or less.
[0134] (Note 3)
[0135] A silicon nitride sintered body according to any one of Notes 1 to 2, wherein, in the above-mentioned area of 20μm×20μm, the difference between the average value of the solid dissolved oxygen content of the above-mentioned silicon nitride crystal particles with a long axis less than 3μm and the average value of the solid dissolved oxygen content of the above-mentioned silicon nitride crystal particles with a long axis greater than 3μm is less than 0.1wt%.
[0136] (Note 4)
[0137] The silicon nitride sintered body according to any one of Supplementary Notes 1 to 3, wherein the grain boundary phase is contained in an amount of 1% by mass or more and 20% by mass or less.
[0138] (Note 5)
[0139] The silicon nitride sintered body according to any one of Supplementary Notes 1 to 4, wherein the maximum value of the major axis of the silicon nitride crystal grains in a 300 μm×300 μm region of an arbitrary cross section is 25 μm or less.
[0140] (Note 6)
[0141] The silicon nitride sintered body according to any one of Supplementary Notes 1 to 5, wherein, when an XRD analysis is performed on an arbitrary cross section, the strongest peak intensity detected at 42.4±0.3° is set as I 42.4° The strongest peak intensities detected at 27.1±0.3°, 33.6±0.3°, and 36.1±0.3° corresponding to β-Si3N4 crystals were set as I 27.1° ,I 33.6° ,I36.1° In the case of 42.4° ) / (I 27.1° +I 33.6° +I 36.1° ) is greater than or equal to 0.005 and less than or equal to 0.030.
[0142] (Note 7)
[0143] The silicon nitride sintered body according to any one of Supplementary Notes 1 to 6, wherein the fracture toughness value is 6 MPa·m 1 / 2 above.
[0144] (Note 8)
[0145] A wear-resistant member using the silicon nitride sintered body according to any one of Supplementary Notes 1 to 7.
[0146] (Note 9)
[0147] The wear-resistant member according to Supplementary Note 8, which is one selected from a bearing ball, a roller, a roll, and a tool member for friction stir welding.
[0148] Several embodiments of the present invention are illustrated above, but these embodiments are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other ways, and various omissions, substitutions, changes, etc. can be made without departing from the scope of the main purpose of the invention. These embodiments and their modifications are included in the scope and main purpose of the invention, and are also included in the invention recorded in the patent claims and their equivalents. In addition, the above-mentioned embodiments can be implemented in combination with each other.
[0149] Explanation of symbols
[0150] 1…Silicon nitride sintered body
[0151] 2…Silicon nitride crystal particles
[0152] 3…Grain boundary phase
[0153] 4…Bearing balls
[0154] 5…Inner ring
[0155] 6…Outer ring
[0156] 10…Bearings
Claims
1. A method for producing a silicon nitride sintered body, comprising the following steps: A step of adding a sintering aid powder in an amount ranging from 1 part by mass to 20 parts by mass to the silicon nitride powder when the total amount of the silicon nitride powder and the sintering aid powder in the raw material powder is set to 100 parts by mass; A mixing step of mixing the raw material powders using a ball mill; A forming step of forming the mixture; A degreasing step of degreasing the formed body; and The sintering step is to sinter the degreased compact. In the mixing step, the raw material powders are mixed by the ball mill using a medium having a diameter of 3 mm or more and 20 mm or less, while the rotation speed of the cylindrical container containing the raw material powders is within the range of 30 rpm or more and 500 rpm or less and the mixing time is within the range of 5 hours or more and 40 hours or less. The obtained silicon nitride sintered body is a silicon nitride sintered body having silicon nitride crystal particles and a grain boundary phase. In a 20 μm×20 μm region of an arbitrary cross section, the average value of the amount of dissolved oxygen in the silicon nitride crystal particles is 0.2 wt % or more, In a 50 μm×50 μm region of an arbitrary cross section, the average value of the major diameter of the silicon nitride crystal particles is 0.1 μm or more and 10 μm or less, and the average value of the aspect ratio of the silicon nitride crystal particles is 1.5 or more and 10 or less, The fracture toughness value of the silicon nitride sintered body is 7MPa·m 1 / 2 above.
2. The method for producing a silicon nitride sintered body according to claim 1, wherein: In the obtained silicon nitride sintered body, the amount of dissolved oxygen in each of the silicon nitride crystal particles present in the region of 20 μm×20 μm is 0.2 wt % or more and 1.5 wt % or less.
3. The method for producing a silicon nitride sintered body according to any one of claims 1 to 2, wherein: In the obtained silicon nitride sintered body, the maximum value of the major axis of the silicon nitride crystal grains in a 300 μm×300 μm region of an arbitrary cross section is 25 μm or less.
4. The method for producing a silicon nitride sintered body according to any one of claims 1 to 2, wherein: The sintering temperature of the sintering step is in a range of 1600° C. to 1900° C.
5. The method for producing a silicon nitride sintered body according to claim 3, wherein: The sintering temperature of the sintering step is in a range of 1600° C. to 1900° C.
6. The method for producing a silicon nitride sintered body according to claim 4, wherein: In the sintering step, the compact is pressurized within a range of 0.2 MPa to 10 MPa while the temperature is raised from 1500° C. to the sintering temperature.
7. The method for producing a silicon nitride sintered body according to claim 5, wherein: In the sintering step, the compact is pressurized within a range of 0.2 MPa to 10 MPa while the temperature is raised from 1500° C. to the sintering temperature.
8. The method for producing a silicon nitride sintered body according to claim 5, wherein: The method further comprises: after the sintering step, performing a HIP step of hot isostatic pressing (HIP) on the silicon nitride sintered body at a temperature within a range of 1500° C. to 1900° C.
9. The method for producing a silicon nitride sintered body according to claim 7, wherein: The method further comprises: after the sintering step, performing a HIP step of hot isostatic pressing (HIP) on the silicon nitride sintered body at a temperature within a range of 1500° C. or higher and 1900° C.
Citation Information
Patent Citations
Gun for underwater stud welding
JP1978062758A
- - Pre-charge which is radar device
JP1989000478A
Method of measuring solid solution oxygen in sintered body of nitride-based ceramic
JP2022071426A
Friction stir welding tool member formed from silicon nitride sintered body and friction stir welding apparatus using same
WO2016047376A1